Global positioning system : Principles and applications - Gopi, Satheesh (Chennai McGraw Hill Education, 2005)
Assuming no prior knowledge of GPS, this book imparts the fundamental knowledge of the Global Positioning System and how to work with it. The book also gives important GPS applications in land mobile, marine navigation, surveying and mapping, space and GIS, etc. In addition to the students, practicing engineers and surveyors too will find this book extremely useful.
Keywords: Civil Engineering